Pengaruh Literasi Keuangan Terhadap Penggunaan Tabungan Mobile Money - Emi Boki; Sari Tamayani Tjio (Program Studi Pendidikan Akuntansi, Fakultas Ekonomi, Universitas Negeri Makassar, 2026)
In Indonesia, especially Maluku, mobile money services are rapidly changing financial inclusion. However, the consistent use of the platform for savings is still limited among micro, small and medium enterprises (MSMEs). This study investigated the role of financial literacy and perceived ease of use in shaping mobile money usage behavior, focusing on the mediating influence of perceived ease of use (PEOU). These findings reveal that financial literacy, and perceived ease of use all have a significant and statistically positive influence on the use of mobile money savings. In addition, PEOU significantly mediates financial literacy in the use of mobile money savings This study is one of the first to holistically examine how financial literacy through ease of use influences mobile money savings behavior among MSMEs. This study contributes as a literature on financial behavior and informs the use of savings for a population that has income from the results of daily business